VLSI-SoC: Internet of Things Foundations 22nd IFIP WG 10.5/IEEE International Conference on Very Large Scale Integration, VLSI-SoC 2014, Playa del Carmen, Mexico, October 6-8, 2014, Revised Selected Papers - Claesen, Luc.; Sanz-Pascual, Maria-Teresa.; Reis, Ricardo; Sarmiento-Reyes, Arturo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book contains extended and revised versions of the best papers presented at the 22nd IFIP WG 10.5/IEEE International Conference on Very Large Scale Integration, VLSI-SoC 2014, held in Playa del Carmen, Mexico, in October 2014. The 12 papers included in the book were carefully reviewed and selected from the 33 full papers presented at the conference. The papers cover a wide range of topics in VLSI technology and advanced research. They address the current trend toward increasing chip integration and technology process advancements bringing about stimulating new challenges both at the physical and system-design levels, as well as in the test of these systems.
Keywords: Computer science; Computer hardware; Computer organization; Computer-aided engineering; Computer Science; Computer Systems Organization and Communication Networks; Computer Hardware; Computer-Aided Engineering (CAD, CAE) and Design; Electronic books